Promoting mathematics problem solving ability through implementing GeoGebra-assisted problem based learning - Dhea Amalia; Intan Indiati; Achmad Buchori; Gunarti Krisnaningsih (Universitas Sarjanawiyata Tamansiswa, 2023)
One of the skills necessary for 21st-century society is the capacity for problem-solving. Students will be required to work in unfamiliar settings, solve problems they have never faced before, and use skills unrelated to any particular subject matter. GeoGebra is a learning environment that provides a variety of representations and simulates various mathematical models. This article aims to describe instructions for the use of Geogebra-assisted PBL in promoting students' capacity for problem-solving. The students who participated in this study consisted of 36 high school students. Mathematics learning is done using the GeoGebra application during the learning process. The method used in this research is descriptive analysis and qualitative research. The specific technique used in implementing GeoGebra-Assisted Problem Based Learning is students through two phases in each sub material. The first phase is focusing on the problems that lead to an understanding about representation for solutions and not solutions in inequality and inequality system. The second phase is focusing on the real world problems that lead to an understanding solving problems using GeoGebra. The results of the study show that teachers need to develop student exploration processes through representations, simulations, problems, and solutions using GeoGebra that are close to student reality. The use of GeoGebra-assisted PBL is mathematics learning is able to support student exploration so that students are more involved in the learning process by paying attention to student interaction and exploration. The use of GeoGebra makes students active knowledge builders, tracks the process of change, and keeps students engaged with teachers in mathematics teaching. The analysis carried out was supported by student learning outcomes, which showed that the average learning outcomes were significantly different and exceeded the Minimum Criteria of Mastery Learning and as many as 86% of students scored above the Minimum Criteria of Mastery Learning. The use of GeoGebra-assisted PBL considerably increased students' capacity for problem-solving, notably in terms of their capacity to recognize issues, obtain data, evaluate it, and suggest solutions. Additionally, students perceived that GeoGebra was a useful tool for accelerating their learning, offering dynamic and interesting learning opportunities, and strengthening their capacity for problem-solving.